Changing Impacts of Tropical Cyclones on East and Southeast Asian Inland Regions in the Past and a Globally Warmed Future Climate - Chen, Jilong; Tam, Chi-Yung; Cheung, Kevin; Wang, Ziqian; Murakami, Hiroyuki; Lau, Ngar-Cheung; Garner, Stephen T.; Xiao, Ziniu; Choy, Chun-Wing; Wang, Peng (Frontiers in Earth Science, 2021)
The impacts of the western North Pacific (WNP) tropical cyclone (TC) on East and Southeast Asian inland region are analyzed. Here, based on a stringent TC selecting criterion, robust increase of TC related inland impacts in 1979-2016 over East and Southeast Asian regions have been detected. The storms have sustained 2-9 hours longer and penetrated 30-190 km further inland, as revealed from different best track datasets. The most significant increase of the TC inland impacts occurred over Hanoi and South China. The physical mechanism that affects the TC related inland impacts are shortly discussed. First, the increasing TC inland impacts just occurs in the WNP region, but not a global effect. Second, besides the significant WNP warming effects on the enhanced TC landfall intensity and TC inland impacts, it is suggested the weakened of the upper-level Asian Pacific teleconnection pattern since 1970s may also play an important role, which may reduce the climatic 200hPa anti-cyclonic wind flows over the Asian region, weakening the wind shear near the Philippine Sea, and may eventually intensify the TC intensity when the TCs across the basin. Moreover, the TC inland impacts in the warming future are projected based on a high-resolution (20 km) global model according to the Representative Concentration Pathway 8.5 scenario. By the end of the 21st century, TC mean landfall intensity will increase by 2 m/s (6%). The stronger storms will sustain 4.9 hours (56%) longer, and penetrate 92.4 km (50%) farther inland, and thereby almost doubling the destructive power delivered to Asian inland regions. More inland locations will therefore be exposed to severe storm-related hazards in the future due to warmer climate. Long-term planning to enhance disaster preparedness and resilience in these regions is called for.